Pengaruh Kinerja Lingkungan, Kinerja Keuangan dan Ukuran Perusahaan Terhadap Environmental Disclosure pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2019 - Rizki Assiva; Eni Kaharti (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
This Research was conducted to determine the effect of environmental performance, financial performance and firm size on environmental disclosure in manufacturing companies listed on the IDX in 2016-2019 with a total of 150 companies. By using the purposive sampling method, 25 manufacturing companies were taken. The analysis technique used is multiple linear regression analysis. The results of this research indicate that environmental performance have an effect on environmental disclosure, financial performance has a negative effect on environmental disclosure, firm size has no effect on environmental disclosure.